Tinjauan Teologis Bubun To’saruran Sebagai Media Penyembuhan Bagi Masyarakat Pangrorean Di Tana Toraja - Tosuli, Natalia; Henri Sirangki (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2024)
The Toraja are a tribe loaded with local wisdom, one of which is bubun to'saruran that exists in Pangrorean. The presence of such dew (wells) is believed to cure various diseases. This is certainly not in line with Christian teachings, which teach that the only healing comes from God. The aim of this study was to describe toologically bubun to'saruran as a medium of healing for Pangrorean people. The method used in this study was a descriptive culitative method with interview techniques and field observation. The result of the research is that the existence of Bubun To'Saruran is a gift of God for the Pangrorean people. Bubun To'Saruran is one of the local wisdom for local people as a medium that can cure diseases. Theologically, the author finds that society does not have dualistic beliefs with the presence of the divination, but is purely theocentric.